2015
DOI: 10.1007/s11356-015-4472-0
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of pesticides using fungi species found in the aquatic environment

Abstract: Relatively limited attention has been given to the presence of fungi in the aquatic environment compared to their occurrence in other matrices. Taking advantage and recognizing the biodegradable capabilities of fungi is important, since these organisms may produce many potent enzymes capable of degrading toxic pollutants. Therefore, the aim of this study was to evaluate the potential ability of some species of filamentous fungi that occur in the aquatic environment to degrade pesticides in untreated surface wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 51 publications
0
25
0
Order By: Relevance
“…Aspergillus species are saprophytic moulds widely distributed in soil, decaying vegetation, dust, bioaerosols and different aquatic environments, in which they are expected to contribute to the degradation of pollutants (Sammon et al 2010;Pereira et al 2013;Pearson et al 2015;Ma et al 2015;Oliveira et al 2015). Aspergillus fumigatus, which is responsible for severe pathologies in humans and birds (Van Waeyenberghe et al 2013), has been isolated from hospital water systems and plumbing drains (Hayette et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Aspergillus species are saprophytic moulds widely distributed in soil, decaying vegetation, dust, bioaerosols and different aquatic environments, in which they are expected to contribute to the degradation of pollutants (Sammon et al 2010;Pereira et al 2013;Pearson et al 2015;Ma et al 2015;Oliveira et al 2015). Aspergillus fumigatus, which is responsible for severe pathologies in humans and birds (Van Waeyenberghe et al 2013), has been isolated from hospital water systems and plumbing drains (Hayette et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It indeed grew almost 4-fold more than the other A. sydowii. to the presence of toxic pesticides and the interaction with the natural microbial population: P. citrinum, A. fumigatus and A. terreus were the most robust to the environmental conditions and actually capable of degrading the spiked chlorfenvinphos (Oliveira et al 2015).…”
Section: Bioremediation Of Oacs By Fungi In Aquatic Ecosystemmentioning
confidence: 99%
“…Mochi et al (2005) showed that some insecticides had no toxic effect on M. anisopliae in the soil, with the exception of trichlorphon, an insecticide of the organophosphorous chemical group, which significantly reduced the respiratory activity of the fungus. In the aquatic environment the fungi Penicillium citrinum, Aspergillus fumigatus, Aspergillus terreus and Trichoderma harziaum were resistant and capable of degrading chlorfenvinphos, an organophosphorous insecticide as chlorpyriphos (Oliveira et al, 2015).…”
Section: Chlorpyriphosmentioning
confidence: 99%